Perkembangan Olahraga Pacu Jawi: Dari Tradisi Budaya hingga Organisasi di Kabupaten Tanah Datar (1990-2024) - Medri, Laura; Najmi, Najmi (Jurusan Sejarah FIS UNP, 2025)
Pacu Jawi is a traditional agrarian festivity of the Minangkabau community that has undergone a significant transformation into a formally organized traditional sport, particularly in Tanah Datar Regency. This study aims to explain the development of Pacu Jawi from 1990 to 2024, tracing its evolution from a post-harvest ritual tradition to the establishment of a formal institution, namely the Persatuan Olahraga Pacu Jawi (PORWI). This research applies historical methods, including the stages of heuristics, source criticism, interpretation, and historiography. Data were collected through literature review, interviews with traditional leaders and PORWI administrators, and documentation of Pacu Jawi events. The findings reveal that the transformation of Pacu Jawi has been influenced by modernization, tourism promotion, and local cultural preservation efforts by the community and local government. Since the formation of PORWI in 2000 and its official recognition in 2021, the governance of Pacu Jawi has undergone structural reform, including the establishment of organizational systems, implementation of procedural standards, and increased financial support from the government. Challenges such as the COVID-19 pandemic and natural disasters were met with adaptive institutional strategies grounded in Minangkabau customary values. Today, Pacu Jawi serves not only as a sporting and cultural performance but also as a symbol of Minangkabau cultural identity and a growing source of local economic potential. This study contributes to the discourse on the history of traditional sports and the dynamics of cultural institutions in Indonesia.